Universal point-of-care detection of proteins based on proximity hybridization-mediated isothermal exponential amplification. Issue 8 (25th March 2022) - Tang, Zibin; Zhao, Wenyong; Deng, Yuling; Sun, Yuanzhong; Qiu, Cailing; Wu, Binhua; Bao, Juan; Chen, Zhangquan; Yu, Luxin
Abstract : A lateral flow biosensor has been fabricated for protein detection based on a protein-to-DNA signal transducer, isothermal exponential amplification and catalytic hairpin assembly with high sensitivity and specificity. Abstract : We have developed a point-of-care (POC) lateral flow biosensor (LFB) for universal protein detection based on a proximity hybridization-mediated protein-to-DNA signal transducer, isothermal exponential amplification (EXPAR) and catalytic hairpin assembly (CHA) with high sensitivity and specificity. In this assay, a protein signal transducer was employed to convert the input protein to the output DNA signal. Antibody conjugated DNA1 was firstly hybridized with the output DNA (DNA3). The binding of antibody conjugated DNA1 and DNA2 to the same protein was able to increase the local concentrations, resulting in strand displacement between DNA3 and DNA2. DNA3 with nicking endonuclease recognition sequences at the 5′ end then hybridized with hairpin probe 1 to mediate EXPAR in the presence of nicking endonuclease and polymerase. A large number of single strand DNA were produced in the circle of nicking, polymerization and strand displacement. The resulting ssDNA products were further amplified by CHA to generate double-stranded DNA products. The double-stranded DNA products were detected with a lateral flow biosensor within 5 min. This proposed assay has very high sensitivity and selectivity with a dynamic response ranging from 1 fM to 100 nM, and the detection limit was 0.74 fM. This work provides a universal and simple method for protein detection.